ANALISIS PELAYANAN ANGKUTAN BUS SEKOLAH GRATIS DI KABUPATEN MIMIKA (Studi Kasus Bus Eks PON pada Dinas Perhubungan) - Nur Azizah; Sunarti, Yahya Nusa (ADISAM PUBLISHER, 2025)
Transport is the transfer of people or cargo from a place of origin to a destination. School buses are multi-capacity vehicles used to transport students to school. This study aims to determine how the Effectiveness of Free School Bus Public Transport Services in Mimika Regency. The method used in this research is a descriptive method with a quantitative approach. The data collection techniques used by researchers are observation, interview and questionnaire techniques. The data analysis instrument used is quantitative analysis using effectiveness analysis tools. The results showed that the effectiveness of Free School Bus Public Transport Services in Mimika Regency was declared effective